2020
DOI: 10.1017/s000711452000392x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol intake and cognitive decline in the Seguimiento Universidad de Navarra (SUN) Project

Abstract: The global growing rates of cognitive decline and dementia, together with the absence of curative therapies for these conditions, support the interest in researching potential primary prevention interventions, with particular focus on dietary habits. The aim was to assess the association between the intake of polyphenols and 6-year change in cognitive function in the “Seguimiento Universidad de Navarra” (SUN) Project, a Spanish prospective cohort study. Changes (final – initial) in cognitive function were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The findings support the beneficial health effects of dietary phenolics including antiplatelet activity [51], antioxidative properties [52] and anti-inflammatory activity [53][54][55]. Furthermore, plant-based diets which provide a reliable source of phenolic compounds are reported to have a potential role in lowering the risk of cognitive disorders [56][57][58].…”
Section: Food and Health Among The Elderlysupporting
confidence: 62%
“…The findings support the beneficial health effects of dietary phenolics including antiplatelet activity [51], antioxidative properties [52] and anti-inflammatory activity [53][54][55]. Furthermore, plant-based diets which provide a reliable source of phenolic compounds are reported to have a potential role in lowering the risk of cognitive disorders [56][57][58].…”
Section: Food and Health Among The Elderlysupporting
confidence: 62%
“…Up to date, solely two observational studies investigated the association between dietary phenolic acid intake and cognitive status [ 34 , 35 ]. A prospective cohort study of 806 elderlies followed-up for 6 years showed a significant inverse association between higher dietary phenolic acid intake and cognitive decline, however, a clear linear trend in the association was not observed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, solely two observational studies investigated the association between dietary phenolic acid intake and cognitive status [ 34 , 35 ]. A prospective cohort study of 806 elderlies followed-up for 6 years showed a significant inverse association between higher dietary phenolic acid intake and cognitive decline, however, a clear linear trend in the association was not observed [ 34 ]. The results of SU.VI.MAX study conducted on 2574 middle-aged adults demonstrated that higher intake of hydroxybenzoic acids was positively associated with language and verbal memory, suggesting that diet high in phenolic acids may favor preservation of the verbal memory [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher baseline total flavonoid intakes were associated with reduced cognitive decline over 10 years [2] and improved executive function in adults with mild to moderate Alzheimer's disease [3]. In contrast, total flavonoids were not associated with cognitive change over 6 years in a Spanish prospective cohort study [4]. Higher intakes of flavonols, anthocyanins and flavonoid polymers were associated with a lower risk of Alzheimer disease, and related dementias in the Framingham Offspring Cohort [5] and higher intakes of flavan-3-ols, flavonols and anthocyanins were positively associated with cognitive status, assessed using the Short Portable Mental Status Questionnaire [6].…”
Section: Introductionmentioning
confidence: 99%